UV photocrosslinked polymeric fluorescent sensor for bisphenol A - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (ELSEVIER SCIENCE BV, 2018)
Bisphenol A (BPA) is known as endocrine disrupting compound and it is widely used as an intermediate in manufacturing of polycarbonate and epoxy resins. These resins are used to manufacture inner surface of food cans or directly contact with food and can release BPA into food. It is known that BPA poses health risk, but how risky is a matter of debate. In this study, selective and sensitive fluorescent polymeric membrane sensor for detection of BPA was developed based on fluorescence quenching (lambda ex/lambda em = 272/295 nm). Working concentration range was linear between 4.4 x 10(-9) mol L-1 and 1.1 x 10(-7) mol L-1 with a detection limit of 1.58 x 10(-9) mol L-1. Optimization of sensor was done and the sensor exhibited satisfactory results for being used as a fluorescent sensor for determination of BPA. Additionally, the proposed method was successfully applied to plastic food containers real samples. The developed sensor was shown to be more sensitive than other methods currently in use, and was able to provide results in a matter of seconds, opening up the possibility of a rapid tool for BPA detection.
Keywords: Selective BPA determination; Fluorimetric sensor; Membrane; Vinylphenylboronic acid; UV- curing; TANDEM MASS-SPECTROMETRY; SELECTIVE DETERMINATION; BPA; FOOD; EXTRACTION; ELECTRODE; SYSTEM; PHASE; WATER